Implementasi Spiritual Accountability Berbasis Nilai-Nilai Islam sebagai Pengendali Internal dalam Mewujudkan Good Governance di Sektor Publik Indonesia - Tadjri Tadjri; Nuril Anwar; Fariz Rahmaditya; Milana Abdillah S. (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Good governance in Indonesia's public sector continues to face serious challenges in the form of corruption, collusion, and nepotism (KKN), despite the existence of comprehensive legal frameworks such as the General Principles of Good Governance (AUPB) and the Government Internal Control System (SPIP). This study aims to analyze the role of Islamic value-based spiritual accountability as an internal control mechanism that can strengthen the realization of good governance. Using a library research method through an integrative content analysis and conceptual synthesis approach, this study examines literature on good governance and AUPB in Indonesian administrative law, public sector accountability and internal control, as well as the concept of spiritual accountability from an Islamic perspective. The synthesis results indicate that spiritual accountability grounded in taqwa, amanah, muhasabah, and ihsan functions as an effective "soft control" that complements the formal internal control components (COSO/SPIP). These values strengthen the tone at the top, encourage honest reporting, and create a continuous monitoring mechanism based on divine awareness. This study proposes a conceptual framework called the Model of Internal Control Based on Islamic Spiritual Accountability (PIBSAI) or Islamic Spiritual Internal Control for Public Governance (ISIC-PG) Framework, which has theoretical implications for the development of public sector accounting and practical implications for strengthening AUPB and bureaucratic reform in Indonesia. Spiritual accountability does not replace the positive legal framework but serves as an internal reinforcer that enables the principles of good governance to be not only formally complied with but deeply internalized.